Leading with political astuteness - a white paper : a study of public managers in Australia, New Zealand and the United Kingdom /: a study of public managers in Australia, New Zealand and the United Kingdom. (2013) - Hartley, Jean, 1953-; Alford, John, 1950-; Hughes, Owen E; (Research fellow), Yates, Sophie
No abstract available